Modification of χc1(3872) and ψ(2S) production in pPb collisions at √s NN = 8.16 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Langenbruch, Christoph; et al. (Physical review letters, 2024)
The LHCb Collaboration measures production of the exotic hadron 𝜒𝑐⁢1⁡(3872) in proton-nucleus collisions for the first time. Comparison with the charmonium state 𝜓⁡(2⁢𝑆) suggests that the exotic 𝜒𝑐⁢1⁡(3872) experiences different dynamics in the nuclear medium than conventional hadrons, and comparison with data from proton-proton collisions indicates that the presence of the nucleus may modify 𝜒𝑐⁢1⁡(3872) production rates. This is the first measurement of the nuclear modification factor of an exotic hadron.